Perancangan Ulang Museum Tekstil Jakarta Dengan Pendekatan Teknologi - Hanifah, Nadhimatul; Cardiah, Tita; Murdowo, Djoko (eProceedings of Art & Design, 2024)
This design project re-examines the interior of the Jakarta Textile Museum to address "museum fatigue" and enhance the visitor experience. The analysis of existing conditions identifies key issues such as passive atmosphere, monotonous displays, and confusing flow. The main objective is to create a dynamic, interactive, and educational museum experience. The methodology includes in-depth analysis, literature review, and design concept development. This research proposes several main solutions utilizing modern technology, reorganizing the exhibition flow based on chronology, and designing innovative display facilities. The observation results in an interior design that transforms the Jakarta Textile Museum into a relevant cultural and educational destination. This design aims to increase visitation, reduce museum fatigue, and establish the museum as a model for adopting optimal educational methods with modern technology. In conclusion, this redesign offers a comprehensive solution to revitalize the Jakarta Textile Museum, enhance its function as an institution for education and cultural heritage preservation, and create a more meaningful experience for visitors in the contemporary era. Keywords: museum, textile, thecnology, interactive, education